Anomalous systemic arterial supply to the left lower lung lobe: A case report - Wu, Zhuo; Xu, Baoning; Zhou, Di; Yang, Xueying (Frontiers in Medicine, 2022)
Background: Anomalous systemic arterial supply to the lung lobes is a rare congenital pulmonary vascular malformation. Current regimens include thoracoscopic lobectomy, anatomical segmentectomy, and simple ligation of the anomalous systemic artery or arterial embolization. However, the optimal regimen remains controversial. Case presentation: A 29-year-old man was diagnosed with an anomalous systemic arterial supply to the basal segments of the left lower lobe through contrast-enhanced computed tomography scan and 3-dimensional reconstruction of the pulmonary arteries. He underwent coil embolization of the anomalous artery and completed a 1-year follow-up. Conclusions: Blockage of the blood flow of the anomalous systemic artery alone does not improve the blood supply of the pulmonary artery to the lung tissue and thus cannot restore normal gas exchange through the blood-gas barrier. Coil embolization of the anomalous arterial supply can cause early postoperative pulmonary infarction.